European Union (EU) Information Security Policies Türkay - Türkay Henkoğlu; Bülent Yılmaz (Türk Kütüphaneciliği)
The development of the European economy is strongly related to the use of Information andcommunication technologies (ICT) and the transformation process of information society. However, because of the risks of ICT, people are anxious about using technology, which in turn retards the economic growth of countries all around the world. Therefore, especially in the last twenty years, information security issues have begun to gain importance in European Community (EC) information policies, and many suggestions have been made related to these issues.